Uzlah dan Zikir Dalam Tafsir Sufi Isharī al-Baḥr al-Madīd Karangan Ibn ‘Ajībah: ‘Uzlah and Dhikr in Sufi Isharī’s Exegesis al-Baḥr al-Madīd by Ibn ‘Ajībah - Hashim, Mahyuddin; Taeali, Asman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Ibn ‘Ajībah has integrated the knowledge of taṣawwuf with the Qur’anic knowledge by writing about the ‘uzlah and dhikr in his Tafsir Sufi Isharī called al-Baḥrul Madīd. Tafsir Sufi Isharī is one of the forms of exegesis to describe the meaning of al-Qur’an. It is an interpretation based on hidden signals that are contrary to the interpretation of the verses of al-Qurʾan. However, this type of interpretation requires a meticulous study, so it is not based on lust as it does by the deviant Shī‘ah Baṭinīyah or it aims to illustrate that the meaning of Allah’s word is too broad. The purpose of this article is to identify Ibn ‘Ajībah’s views about ‘uzlah and dhikr in al-Baḥr al-Madīd. Then, it will evaluated the interpretation of Ibn ‘Ajībah in his works whether it is coincides with the requirements set by the scholars or not. This research is based on the textual study by using content analysis method in criticism and evaluation. Generally, Ibn ‘Ajībah has outlined his views regarding ‘uzlah and dikr. Some of his views are coincide with the requirements and conditions by ‘ulama’ while some others are contrary to what is outlined.